PENGARUH MODEL QUANTUM LEARNING DENGAN FORMASI TEMPAT DUDUK CORAK TIM TERHADAP HASIL BELAJAR SISWA KELAS IV SDN KABONGAN KIDUL REMBANG - Shinta Ayu Suryaningtyas; Nur Khoiri; Ervina Eka Subekthi (Jurnal Guru Kita PGSD, 2018)
Abstract: Influence of Quantum Learning Model With Sitting Formation ofTeam Towards Students Learning Outcomes of Class IV SDN Kabongan KidulRembang. This study aims to determine the effect of the application of learningmodel of quantum learning with the formation of the team style seating on the resultsof fourth grade students of SDN Kabongan Kidul Rembang. This type of research isquantitative research type experiment with pre-experimental design type that is onegrouppretest-posttest design. The population of this research is the fourth gradestudents at SDN Kabongan Kidul Rembang. The sample of this research is allstudents of grade IV SDN Kabongan Kidul Rembang academic year 2017/2018which amounted to 35 students. Data collection using interviews, tests, observationsand documentation. The research results obtained pretest average of 59.65 while theaverage posttest of 83.71. So it can be concluded that the quantum learning modelwith the formation of the seating pattern of the team has an effect on the students'achievement of fourth grade SDN Kabongan Kidul Rembang.Keyword : Quantum Learning Model, Seating Formation, Learning OutcomesAbstrak : Pengaruh Model Quantum Learning Dengan Formasi Tempat DudukCorak Tim Terhadap Hasil Belajar Siswa Kelas IV SDN Kabongan KidulRembang. Penelitian ini bertujuan untuk mengetahui pengaruh penerapan modelpembelajaran quantum learning dengan formasi tempat duduk corak tim terhadaphasil belajar siswa kelas IV SDN Kabongan Kidul Rembang. Jenis penelitian iniadalah penelitian kuantitatif tipe eksperimen dengan jenis pre-experimental designyakni one-group pretest-posttest design. Populasi penelitian ini adalah siswa kelasIV di SDN Kabongan Kidul Rembang. Sampel penelitian ini yaitu semua siswasiswikelas IV SDN Kabongan Kidul Rembang tahun ajaran 2017/2018 yangberjumlah 35 siswa. Pengambilan data menggunakan wawancara, tes, observasi dandokumentasi. Hasil penelitan diperoleh rata-rata pretest yaitu sebesar 59,65sedangkan hasil rata-rata posttest sebesar 83,71. Jadi dapat disimpulkan modelquantum learning dengan formasi tempat duduk corak tim berpengaruh terhadaphasil belajar siswa kelas IV SDN Kabongan Kidul Rembang.Kata Kunci : Model Quantum Learning, Formasi Tempat Duduk, Hasil Belajar